Three Decades of Public Attitudes Research on Crime and Punishment in Canada - Varma, Kimberly N.; Marinos, Voula (Canadian Journal of Criminology and Criminal Justice, 2013)
Three decades of research on public perceptions in Canada has fundamentally shifted academic and policy approaches to understanding public views of crime and punishment. The contributions of Anthony Doob and his colleagues have influenced methodology, such as the inclusion of experimental design, and have supported an underlying commitment to understanding the public's view of crime and its relationship to policy. This article examines key findings coming out of this body of research and the impact of this work on current criminal justice policy in Canada. Despite the significance of this body of work on public perceptions research, the impact on current criminal justice policy appears to be diminishing.